Fast and Beautiful Web Development Using React and Tailwind Css - Suhendar , Achmad; Razani , Muhammad Naufal; Sutowo , Muhammad Haidar Althaaf; Pratama , Nur Fauzta Putra; Darmawan , Zuhair Fakhriy Al Faarisi; Ambo , Sitti Nurbaya; Mujiastuti , Rully; Risanty , Rita Dewi; Sutrisno , Mirza (Dedication : Jurnal Pengabdian Masyarakat, 2026)
The development of modern web technologies requires developers to build user interfaces that are interactive, responsive, and visually appealing in an efficient manner. However, beginner developers often encounter difficulties in managing code structure and interface design effectively. This webinar and workshop aimed to enhance participants’ understanding and skills in developing modern portfolio websites using React and Tailwind CSS. The activities were conducted online through webinar sessions and hands-on workshops (live coding), involving 26 participants. Evaluation was carried out using pre-tests and post-tests to measure learning improvement. The results indicated an increase in the average correct response rate from 77% in the pre-test to 91.6% in the post-test, representing a 14.6% improvement. In addition, participant feedback showed a high level of satisfaction, with 54.2% reporting being very satisfied and 33.3% satisfied. The output of this activity was a responsive portfolio website serving as the participants’ digital identity.